Study the influence of the anodizing process parameters on the anodized copper hardness - Mahmood, Mahmood Hameed; ,, Suryanto; Hazza Faizi Al Hazza, Muataz; Haider I., Farag (EDP Sciences, 2017)
Abstract. The metals anodization process used to enhance the surface hardness and corrosion resistance. This study developed a durable hard Nano copper oxide coating on copper using anodization technique in solutions of 0.1 to 0.5 M oxalate concentrations and 0 to 24οC operating temperature. The settings of the process parameters determined by using Taguchi’s experimental design method. The EDX and XRD results confirm the formation of cupric oxide coating with monoclinic lattice crystalline structures. The FESEM results for the coated samples showed that the grain size was in the range between 25 to 68 nm. Microhardness tests for the anodized copper samples characterized by microhardness tester. Analysis of Variance for the orthogonal arrays of Taguchi identified that the most affecting parameter on the microhardness of the coating was the anodizing temperature. The results show that the hardness of the anodized coating was decreased with the anodizing temperature, where maximum hardness, with smaller grain size,wereproducedatloweranodizingtemperatures.